2015
DOI: 10.1177/0022034514565646
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization Behavior of Hydrophilic-Rich Phase of Dentin Adhesive

Abstract: The 2-fold objectives of this study were 1) to understand whether model hydrophobic-and hydrophilic-rich phase mimics of dentin adhesive polymerize similarly and 2) to determine which factor, the dimethacrylate component, bisphenol A glycerolate dimethacrylate (BisGMA) or photoinitiator concentration, has greater influence on the polymerization of the hydrophilic-rich phase mimic. Current dentin adhesives are sensitive to moisture, as evidenced by nanoleakage in the hybrid layer and phase separation into hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 30 publications
1
36
2
1
Order By: Relevance
“…Combination of these events leads to phase separation, as already described. [22][23][24][25] However, it is important to highlight that phase separation may be even more severe where C=C conversion is higher, such as for these groups formulated with BAPO and TPO, unless the rate of reaction is very fast. Although it was already demonstrated that phosphine-oxide-based initiators might develop faster reaction than CQ, 18 the photopolymerization kinetics was not determined for the materials tested in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of these events leads to phase separation, as already described. [22][23][24][25] However, it is important to highlight that phase separation may be even more severe where C=C conversion is higher, such as for these groups formulated with BAPO and TPO, unless the rate of reaction is very fast. Although it was already demonstrated that phosphine-oxide-based initiators might develop faster reaction than CQ, 18 the photopolymerization kinetics was not determined for the materials tested in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in a cloudy mixture since 33 wt% of D 2 O was above the miscibility limit for this formulation [14]. Then, the photo-initiators were replenished based on the quantity of D 2 O added so that the final composition of each photo-initiator reached 0.5 wt%.…”
Section: Methodsmentioning
confidence: 99%
“…Then a plastic cover slip was placed on it. The edges of the coverslip were sealed using tape to prevent evaporation of D 2 O from the sample; D 2 O evaporation could cause variation in the polymerization kinetics [14, 15]. The D 2 O profile was also monitored to ensure that there was no evaporation of D 2 O and the initial slight changes in the profile could be related to diffusion, either away from or towards the ATR crystal, within the sample [15].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations